OPTIMIZATION OF SCHOOL EDUCATIONAL MANAGEMENT: ACADEMIC EVALUATION AND SUPERVISION - Poncowati, Srikandi Dwi (Jurnal Konseling Pendidikan Islam, 2024)
The objective of this research is to optimise school education management through academic evaluation and supervision. The method employed in this research is qualitative research, specifically using a case study approach. The use of a case study is chosen because it allows the researcher to deeply understand the context, processes, and complexities of the phenomenon under investigation. The research findings indicate that the optimisation of education management has made significant progress through the evaluation and supervision conducted by school principals and relevant supervisors. However, challenges such as additional workload, the need for leadership skill enhancement, and the involvement of parents and the community still need to be addressed. Strategic steps that can be taken to overcome these challenges include increased investment in professional training and development, expanded collaboration with external parties, and the strengthening of the role of parents and the community in evaluation and supervision. Other measures involve implementing mentoring programmes, advocating for changes in the education system, and investing in educational technology infrastructure.